Sistem Pelaksanaan Promosi Kesehatan di Rumah Sakit X Kabupaten Gresik Berdasarkan Standar Peraturan Menteri Kesehatan No. 44 Tahun 2018 - Nabila Madhuri Rania Nasuha; Lathiifah Amalia Rihtianti (Universitas Airlangga, 2024)
Background: Hospitals in Indonesia are required to carry out health promotions based on the latest Minister of Health Regulation, namely Minister of Health Regulation Number 44 of 2018 to increase the willingness, awareness and ability to live a clean and healthy life for patients, patient families, hospital visitors and residents near the hospital. Objectives: To provide an overview of implementing hospital health promotion program. The method used in this study is descriptive qualitative through observation and in-depth interviews in accordance with Permenkes Number 44 of 2018. Methods: The method used was descriptive qualitative through observation and in-depth interviews in accordance with the Minister of Health Regulation Number 44 of 2018. The research subject was the health promotion team of Ibnu Sina Hospital, Gresik Regency. Data collection by observation, literature study, in-depth interviews, and activity lectures. Data analysis by observing what is appropriate or not then connected to the theory with an explanation. Results: The description of the implementation of PKRS (Hospital Health Promotion) at Ibnu Sina Regional General Hospital with Minister of Health Regulation Number 44 of 2018 regarding the Implementation of Hospital Health Promotion is good and in line with implementation targets. Conclusions: Ibnu Sina Regional Hospital in implementing PKRS (Hospital Health Promotion) has innovations and improvements made for the welfare of the hospital community. It is appealed to the Ibnu Sina Regional Hospital and the PKRS (Hospital Health Promotion) Team to maintain and improve the image of hospitals in Indonesia as well as being an example of hospitals in Gresik Regency.